Science, Information, and Policy Interface for Effective Coastal and Ocean Management - Bertrum H. MacDonald; Suzuette S. Soomai; Elizabeth M. De Santo; Peter G. Wells (CRC Press, 2016)
This book provides a timely analysis of the role that information-particularly scientific information-plays in the policy-making and decision-making processes in coastal and ocean management. It includes contributions from global experts in marine environmental science, marine policy, fisheries, public policy and administration, resource management